Factors that influence employee’s retention rate in financial technology startups in Indonesia - M Asbullah; Saefudin Zuhri; Muhammad Nur Abdi (Privietlab, 2022)
The current human resource management (HR) and brand marketing (Employer Branding) issues are recruiting and retention approaches that 'involve internally and externally encourage a clear vision of what makes a business different and attractive as a business. Sampling is done using probability sampling techniques, namely sampling techniques that provide equal opportunity or opportunity for each member of the population to be selected as a sample. This method is carried out when members of the population are considered homogeneous to financial technology stratups employees. The results of this study explain that there are several important factors that can affect employee retention at financial technology stratups companies, one of which is compensation and recognition which have a significant effect on employee retention. Motivation is the variable that has the greatest influence on employee retention, apart from having a direct effect on motivation, motivation has also succeeded in being a mediator between compensation for employee retention and recognition of employee retention.